Sosialisasi Penanganan Permasalahan Sistem Reproduksi Dan Infertilitas Pada Wanita Melalui Webinar - Sembiring, Julina; Kadir, Dalimawaty; Sukatendel, Khairani (Window of Community Dedication Journal, 2021)
Disorders of the female reproductive organs can be caused by many things. If left untreated, some of these diseases of the female reproductive system can even increase a woman's risk of experiencing fertility problems. The female reproductive system consists of the labia majora, labia minora, Bartholin's glands, clitoris, vagina, uterus or uterus, ovaries (ovaries), and fallopian tube. The female reproductive system is a very complex body system, so steps are needed to protect this system from infection and injury. In addition, it is necessary to prevent problems that may occur in the female reproductive system, including long-term health problems. Maintaining the reproductive system is the same as maintaining personal health, especially during pregnancy. This service activity aims to increase public knowledge about the Handling of Reproductive System Problems and Infertility in Women. The method used is socialization through a webinar entitled "Handling Reproductive System Problems and Infertility in Women by using the Zoom application, adjusted to the current situation of the Covid 19 pandemic. The webinar activity was attended by 130 participants, consisting of 2 presenters, 1 lecturer as moderator, and 127 midwives from the hospital working area of ​​North Sumatra. After the webinar was conducted, Improving the Skill / skills of midwives to detect problems with women's health, being able to provide first aid in reproductive health cases and Motivating all participants that midwives are able to continue to stand and provide services for future generations